Pengaruh Kepemilikan Manajerial, Kompensasi Bonus Terhadap Manajemen Laba Saat Sebelum dan Sesudah Kebijakan “PSBB” Diberlakukan Pada Sektor Industri Transportasi dan Logistik - William Kwestianus; Alby Tandinata; Yulius Christiawan (Business Accounting Review, 2021)
Agency theory is the employment relationship between the agent and the principal. Differences ininterests cause agency problems where the decisions taken by the agent are not in line with the principal. Theprincipal tendency to make profit as an indicator of company performance is the main reason why earningsmanagement practices occur. The existence of the "PSBB" policy affects the company's profit. Managerialownership, bonus compensation can affect the magnitude of earnings management practices. Based on thistheory, this study aims to prove the effect of managerial ownership, bonus compensation on earningsmanagement before and after the "PSBB" policy was implemented. The study was conducted on 15 companiesin the transportation and logistics industry sector on the Indonesia Stock Exchange (IDX) for the 2018-2021.This research uses multiple linear regression technique of panel data. The results of the study prove that thesmaller the managerial ownership and the greater the bonus compensation received by the management, thehigher the earnings management practice. Furthermore, it is proven that the existence of the "PSBB" policyfurther strengthens the negative influence of managerial ownership and strengthens the positive effect of bonuscompensation on earnings management practices.